Assessment of nicotine dependence among cigarette smokers seeking oral health care using fagerström test for nicotine dependence: A cross-sectional study - Nalini Parimi; Nalini Bikkina; Vikram Simha Bommireddy; Morampudi Tejaswi; Sirija Edupalli; V Srujana Krishna Adapa (Wolters Kluwer Medknow Publications, 2022)
Introduction: In the quest of articulating customized tobacco cessation strategies, evaluation of the level of nicotine dependence among participants is quintessential. Objective: This study was conducted to assess the levels of nicotine dependence and its association with age and socioeconomic status among patients seeking oral health care at a teaching dental institution in coastal Andhra Pradesh. Materials and Methods: This cross-sectional study was done among 199 participants with the habit of cigarette smoking who participated in the study. Nicotine dependence scores were assessed using Fagerström Test for Nicotine Dependence (FTND). IBM SPSS version 20 software was used for data analysis. The Chi-square tests and Kruskal-Wallis analyses of variance were done to analyze the study data. P ≤0.05 was considered statistically significant. Results: The mean FTND score was 4.52 ± 2.1. Significant differences in the mean nicotine dependence score were found between different age groups (P < 0.001) and participants belonging to different socioeconomic strata (P < 0.001). While a positive correlation was observed between age and FTND score, an inverse relation was noted between FTND score and socioeconomic status with participants from lower socioeconomic status demonstrating higher FTND scores. The majority of the participants reported smoking <10 cigarettes per day. Conclusion: The study participants demonstrated moderate nicotine dependence. The assessment of nicotine dependence scores as a preliminary step in tobacco cessation counseling is essential to effectively articulate customized cessation strategies.